ERP Responses to Regional Accent Reflect Two Distinct Processes of Perceptual Compensation - Voeten, Cesko C.; Levelt, Clara C. (Frontiers in Neuroscience, 2019)
Humans possess a robust speech-perception apparatus that is able to cope with variation in spoken language. However, linguists have often claimed that this coping ability must be limited, since otherwise there is no way for such variation to lead to language change and regional accents. Previous research has shown that the presence or absence of perceptual compensation is indexed by the N400 and P600 components, where the N400 reflects the general awareness of ‘accented’ speech input, and the P600 responds to phonological-rule violations. The present exploratory paper investigates the hypothesis that these same components are involved in the accommodation to sound change, and that their amplitudes reduce as a sound change becomes accepted by an individual. This is investigated on the basis of a vowel shift in Dutch that has occurred in the Netherlands but not in Flanders (the Dutch-speaking part of Belgium). Netherlandic and Flemish participants were presented auditorily with words containing either conservative or novel vowel realizations, plus two control conditions. Exploratory analyses found no significant differences in ERPs to these realizations, but did uncover two systematic differences. Over nine months, the N400 response became less negative for both groups of participants, but this effect was significantly smaller for the Flemish participants, a finding in line with earlier results on accent processing. Additionally, in one control condition where a ‘novel’ realization was produced based on vowel lengthening, which cannot be achieved by any rule of either Netherlandic or Flemish Dutch and changes the vowel’s phonemic identity, a P600 was obtained in the Netherlandic participants, but not in the Flemish participants. This P600 corroborates a small number of other studies which found phonological P600s, and provides ERP validation of earlier behavioral results that adaptation to variation in speech is possible, until the variation crosses a phoneme boundary. The results of this exploratory study thus reveal two types of perceptual-compensation (dys)function: on-line accent processing, visible as N400 amplitude, and failure to recover from an ungrammatical realization that crosses a phoneme boundary, visible as a P600. These results provide further insight on how these two ERPs reflect the processing of variation.